Design and Fabrication of a Locally Made Plastic Shredder - Olodu, Dickson David; Aluya, Faith Onosetale; Walters, Salvation; Falobi, Blessing Aanuoluwapo (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
Plastic waste management is a growing environmental concern due to the increasing production and disposal of plastic materials, which contribute to pollution and ecological degradation. Conventional plastic shredders are often expensive and inaccessible to small-scale recyclers, necessitating the development of cost-effective and locally fabricated alternatives. The project focuses on designing and fabricating a locally made plastic shredder that addresses plastic waste management challenges. The methodology involved a series of steps including needs assessment, literature review, conceptual and detailed design, material selection, fabrication, assembly, testing, and optimization. The shredder was designed to be cost-effective and efficient, utilizing locally available materials and expertise. Materials used included Aluminium and steel alloys for the frame, copper wire for the motor, high-quality bearings, rubber seals, and various electrical components. Tools employed in the fabrication process ranged from hand tools and power tools to welding equipment and testing instruments. Safety gear was also emphasized to protect workers during the fabrication and operation processes. The testing phase covered functional testing, load testing, efficiency testing, safety assessments, durability testing, environmental testing, and quality control inspections. Design calculations focused on parameters such as shredding capacity, torque, shear force, blade design, hopper volume, material feed rate, structural integrity, energy consumption, and shredder efficiency. Results indicated that the locally made plastic shredder effectively shredded various types of plastic waste, with a satisfactory shredding capacity of 0.21 kg/hr and a shredder efficiency of 83.12%. The torque transmitted by the shaft was 62.50 Nm, and the shear force required to cut through plastic was 2843.5 N. The blade speed was calculated at 41.89 rads/sec, with a cutting speed of 4189 m/sec. The energy consumption of the shredder was 4.48 Kwh. The project concluded that locally made plastic shredders could significantly contribute to sustainable plastic waste management, resource conservation, and environmental protection.